110k views
4 votes
Simplify (4x– 4)– 3. A. –64x9 B. –8x12 C. D.

User Snowy
by
5.4k points

2 Answers

1 vote
(4x - 4) - 3 simplified = 4x -7
User Albinoswordfish
by
6.4k points
2 votes

Answer:


(x^(12))/(64)

Explanation:

Given:
(4x^(-4))^(-3)

We need to simplify it

Here we have exponent of exponent

Exponent law:


(a^m)^n=a^(mn)


a^(-m)=(1)/(a^m)

First we distribute the exponent -3 with each term inside the bracket.


\Rightarrow (4x^(-4))^(-3)


\Rightarrow 4^(-3)(x^(-4))^(-3)


\Rightarrow 64^(-1)x^(-4\cdot -3)


\Rightarrow 64^(-1)x^(12)


\Rightarrow (x^(12))/(64)

Hence, The simplified expression is
\Rightarrow (x^(12))/(64)

User Valerio Versace
by
5.6k points